The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1587/elex.8.802
|View full text |Cite
|
Sign up to set email alerts
|

Power dependence of fiber fuse propagation with a long-period damage track in hole-assisted fiber

Abstract: Abstract:We investigated the dynamics of fiber fuse propagation with a long-period damage track and its power dependence in holeassisted fiber. When the input power is high, the fiber fuse velocity changes greatly over the propagation distance. However, when the input power is low, the velocity change is small and the fiber fuse propagates in almost the same way as in a conventional single-mode fiber. We found that the fiber fuse propagation becomes unstable when the input power exceeds 4.7 W at a wavelength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
(11 reference statements)
2
7
0
Order By: Relevance
“…When the front of the optical discharge reached the splice point, the front shape of the optical discharge changed as shown in Figure 3b. Since the optical discharge is a high temperature fluid [2,16], we consider that its front shape shown in Figure 3b indicates a jet of high temperature fluid that penetrates the air holes of the PCF [38]. After 0.1 ms the optical discharge became small as shown in Figure 3c, and then terminated as shown in Figure 3d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the front of the optical discharge reached the splice point, the front shape of the optical discharge changed as shown in Figure 3b. Since the optical discharge is a high temperature fluid [2,16], we consider that its front shape shown in Figure 3b indicates a jet of high temperature fluid that penetrates the air holes of the PCF [38]. After 0.1 ms the optical discharge became small as shown in Figure 3c, and then terminated as shown in Figure 3d.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in a reduction in the fluid pressure and its temperature. Then, the fiber fuse terminated [38]. The propagation characteristics of the fiber fuse in HAF depend on the relationship between the diameter of an inscribed circle linking the air holes c and D melted [18,20].…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers observed the dynamics of fiber fuse termination near a splice point between a HAF and an SMF by using a high-speed camera [42], [46], [48], [51].…”
Section: Simulation Of Fiber Fuse In Hafmentioning
confidence: 99%
“…The mechanism of fiber fuse termination in HAF can be explained as follows [57]. When D melted is larger than 2R In as shown in Figure 20A, the optical discharge reaches the air holes.…”
Section: Propagation Characteristics Of Fiber Fuse In Hafmentioning
confidence: 99%
“…Furthermore, it has been found that the fiber fuse propagation in HAF depends not only on 2R In but also on d [57].…”
Section: Propagation Characteristics Of Fiber Fuse In Hafmentioning
confidence: 99%